THE INFLUENCE OF LEADERSHIP AND WORKLOAD ON TURNOVER INTENTION WITH JOB SATISFACTION AS AN INTERVENING VARIABLE (CASE STUDY ON EMPLOYEES OF PT USAHA KARYA KENCANA) - Syifa Annisa Yasmin Zain; Rauly Sijabat; Bayu Kurniawan (Jurnal Ekonomi, 2023)
This study examines and analyzes the effect of leadership and workload on turnover intention with job satisfaction as an intervening variable. In this study using quantitative research methods with primary data sources. The sampling technique in this study used the maximum likelihood (ML) technique. Respondents in this study were employees at PT Usaha Karya Kencana involving 100 employees. Data in the study used a seven-point likert scale measurement and were then collected through the distribution of the google form. The data analysis technique uses structural equation modeling (SEM) with the AMOS version 24 application tool. The results show that leadership has a negative effect on turnover intention, workload has a positive effect on turnover intention, leadership has a positive effect on job satisfaction, workload has a negative effect on job satisfaction, job satisfaction has a negative effect on turnover intention, leadership has no effect on mediated turnover intention by job satisfaction, workload affects turnover intention which is mediated by job satisfaction. It is hoped that future research will take variables that have not been studied about turnover intention, producing a wide and different research range.